1633 Va. Acts 219, Acts Made by the Grand Assembly, Holden At James City, August 21st, 1633, An Act That No Arms or Ammunition Be Sold To The Indians, Act X - (:unkn) unknown (My University, 1633)
It is ordered and appointed, That if any person or persons shall sell or barter any guns, powder, shot, or any arms or ammunition unto any Indian or Indians within this territory, the said person or persons shall forfeit to public uses all the goods and chattels that he or they then have to their own use, and shall also suffer imprisonment during life, the one half of which forfeiture shall be to him or them that shall inform and the other half to public uses.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES; TRANSFER